Uji Aktivitas Antihiperglikemia Jus Bit Merah (Beta vulgaris L.) Pada Tikus Putih Jantan Yang Diberikan Beban Glukosa Oral - Sianipar, Artha Yuliana; Br Waruwu, Tasya Sevrina Nica Arlin; Rezza Fikrih Utama; Rialita Lifiani; Mainal Furqan (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Plants containing secondary metabolites of alkaloids, flavonoids, saponins and tannins are known to have antihyperglycemic activity. One of the plants known to contain these secondary metabolites is red beet (Beta vulgaris L.). The purpose of this study was to determine the antihyperglycemic activity of red beetroot juice and to determine the effective concentration of red beetroot juice in reducing blood glucose levels in male rats that were given a glucose load orally. This study uses an experimental method with pretest-posttest control group design, where the test animals used were 25 male white rats divided into 5 groups. Group I was given 0.5% CMC suspension as a negative control, group II was given metformin suspension 9 mg/200 g BW as a positive control, group III was given red beet juice with a concentration of 100%, group IV was given red beet juice with a concentration of 50%, group V given red beet juice concentration of 25%. The results showed that 100% concentration of red beet juice, 50% concentration of red beet juice, and 25% concentration of red beet juice could reduce blood glucose levels in white rats, where red beet juice concentration of 25% had the lowest antihyperglycemic activity, red beet juice concentration of 50 % was not significantly different from metformin as a comparison, and 100% concentration of red beetroot juice had the highest antihyperglycemic activity. It was concluded that red beetroot juice has activity as an antihyperglycemic and the most effective as an antihyperglycemic is 100% concentration of red beetroot juice.